The rookie - Ciardi, Mark.; Gray, Gordon; Johnson, Mark.; Hancock, John Lee.; Quaid, Dennis; Griffiths, Rachel, 1968-; Hernandez, Jay, 1978-; Cox, Brian, 1946-; Grant, Beth, 1949-; Jones, Angus T.; Gonzalez, Rick, 1979-; Schwartzman, John.; et al. ([United States] : Walt Disney Home Entertainment, 2002)
When a shoulder injury ended his minor league pitching career twelve years ago, Jim Morris resorted to the next best thing - coaching. But Jim's team, knowing their coach is a great ball player, makes a deal with him - if they win the district championship, they want Jim to try out for a major-league organization.
Title from DVD label.
Inspired by the real-life rookie, Jim Morris.
MPAA rating: G.
Dennis Quaid, Rachel Griffiths, Jay Hernandez, Brian Cox, Beth Grant, Angus T. Jones, Rick Gonzalez, Chad Lindberg, Angelo Spizzirri.
Cinematography, John Schwartzman ; Editor, Eric L. Beason ; Music, Carter Burwell ; Producers, Mark Ciardi, Gordon Gray and Mark Johnson ; Writer, Mike Rich ; Director, John Lee Hancock.
Audio commentrary - Dennis Quaid and director John Lee Hancock ; "The Inspirational Story of Jim Morris" - meet the real rookie ; Spring Training : Baseball Tips ; Deleted Scenes Introduced by Director John Lee Hancock ; Dolby Digital 5.1 Surround Sound ; Fullscreen (1.33:1) ; French Language Track ; Spanish Subtitles.
Keywords: Morris, Jim, -- 1964- -- Drama; Baseball coaches -- Drama; Pitchers (Baseball) -- Drama; Feature films; Video recordings; Baseball films; Biographical films